2017
DOI: 10.1007/s00234-017-1920-1
|View full text |Cite
|
Sign up to set email alerts
|

New prognostic factor telomerase reverse transcriptase promotor mutation presents without MR imaging biomarkers in primary glioblastoma

Abstract: Imaging biomarkers for prediction of TERT mutation status remain weak and cannot be derived from the VASARI protocol. Tumor-associated seizures are less common in TERT mutated glioblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Taken together with our findings, this supports the idea that in TERT‐wildtype tumors, mechanisms other than BBB disruption may play a larger role in tumor pathogenesis than in TERT‐mutated tumors. Few studies have examined the relationship between VASARI features and mutational status with only one other study specifically examining TERT, which found no significant difference in any of the VASARI features between TERT‐mutated and TERT‐wildtype groups . Differences in results may be secondary to interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Taken together with our findings, this supports the idea that in TERT‐wildtype tumors, mechanisms other than BBB disruption may play a larger role in tumor pathogenesis than in TERT‐mutated tumors. Few studies have examined the relationship between VASARI features and mutational status with only one other study specifically examining TERT, which found no significant difference in any of the VASARI features between TERT‐mutated and TERT‐wildtype groups . Differences in results may be secondary to interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the relationship between VASARI features and mutational status with only one other study specifically examining TERT, which found no significant difference in any of the VASARI features between TERT-mutated and TERT-wildtype groups. 13 Differences in results may be secondary to interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In bladder cancer, besides being associated with an increased disease recurrence and poor patient outcome, the specificity of the TERT promoter mutations distinguishes histologically deceptive cancers from benign mimics 88,112 . In gliomas, the TERT promoter mutations associated with high disease grade, worst patient survival, and other markers follow histological classification into subgroups with distinct disease outcomes 75,[113][114][115][116][117][118][119] . An investigation based on editing out of the TERT promoter mutations showed that the local injection of adenine base editor fused to Campylobacter jejuni CRISPR-associated protein 9 inhibited the growth of gliomas harboring those alterations 120 .…”
Section: Impact Of Tert Promoter Mutationsmentioning
confidence: 99%